On temporally bounded quantification over eventualities - Móia, Telmo (ZAS Papers in Linguistics, 2006)
This paper focuses on different subtypes of constructions involving temporally bounded quantification, e.g. sequences like David visited Rome three times followed by temporal phrases as different as (i) last year, which defines a time interval; (ii) in less that two months, which defines an amount of time; and (iii) per month, which refers to a time unit. As for the first two types of temporal phrases, data will be presented which shows that they have specific linguistic properties in these quantifying contexts, and do not behave exactly as the locating or duration adverbials they are superficially identical with. The third type of phrases will receive special attention. Structures with frequency adverbials like n times per month will be analysed compositionally, separating the quantified component n times from the temporally binding phrase per month (whose role is comparable to that of adverbials (i) and (ii) in the relevant constructions). The data presented is mainly from Portuguese, although the issues at stake – the linguistic properties of temporally bounded quantification – are obviously relevant to parallel constructions in other languages.